Micronecta griseola Horvath, 1899 - a new species of the family Corixidae (Heteroptera) for the fauna of the Middle Urals - Elena Kanyukova; Vitaly Stolbov; Sergey Ivanov (Biodiversity Data Journal, 2021)
Micronecta (Micronecta) griseola Horvath, 1899 is a representative of water bugs of the family Corixidae. It is expanding its range eastwards according to our observations in Russia. In the last decade, the species has become more common in Western Siberia.The article presents the first records of M. griseola from the territory of the Middle Urals (Russia). The distribution of the species and the features of its biology are considered.